Beneficial utilization of drinking-water treatment residuals as contaminant-mitigating agents - O'Connor, George A.; Makris, Konstantinos C. (My University, 2007)
Waste recycling and re-utilization are two energy-efficient processes that have gained popularity due to environment-friendly and cost-reductive advantages. This chapter deals with an example of such processes: the beneficial utilization of the waste by-product generated from the drinking-water treatment process as cost-effective sorbents for contaminants, such as arsenic (As) and phosphorus (P). Drinking-water treatment residuals (WTRs) are primarily amorphous masses of iron (Fe), aluminum (Al) hydroxides or CaCO3 that also contain sediment and humic substances removed from the raw water, as well as coagulating agents added to raw water, such as activated carbon and polymers. WTRs are produced in large quantities at the drinking-water treatment plants and are typically disposed of in landfills. This chapter begins with WTR-relevant definitions and types of WTRs produced, and explains how WTRs are produced. Regulations and alternatives for WTR disposal are discussed. General physical and chemical properties of different types of WTRs are presented. Most of the WTR-pertinent literature focuses on P immobilization by WTRs in poorly P-sorbing soils, and the long-term stability of sorbed P. The data suggest that land application of WTR can be a best management practice to reduce the environmental effects of P. We also discuss the potential for using WTRs as sorbents for arsenic (As). Potential limitations associated with WTR use are discussed, and future research needs addressed.
Keywords: Drinking-water treatment; Arsenic (As); Phosphorus (P); Water treatment residuals (WTRs)